LITERATURE REVIEW: COGNITIVE CONFLICT APPROACH IN PHYSICS LEARNING TO OVERCOME THE MISCONCEPTION OF PHYSICS - Siti Aniatu Sa'adah; Rudi Haryadi (Program Studi Pendidikan IPA FKIP Universitas Jember, 2020)
The misconception is one of the problems in learning physics at school. From several studies that have been done, it is found that many students have misconceptions that affect students in learning and understanding the concepts of physics. This study aims to collect data and analyze articles related to approach efforts. Cognitive conflict in physics learning to overcome misconceptions of physics. The design used is a literature review. The articles were collected using a search engine, namely Google Scholar. Based on the articles collected, the results showed that the students' failure to connect a physics concept that had been studied was a factor of physics my conception. This ultimately affects student learning outcomes. The role of the teacher in this learning is that students are used as learning objects as passive recipients of the information who only listen and take notes. And try to explore development. envision the ability of students to think critically which leads to the formation of a more independent student character.